Charge Density Wave Orders and Enhanced Superconductivity under Pressure in the Kagome Metal CsV3Sb5. Issue 42 (3rd September 2021) - Wang, Qi; Kong, Pengfei; Shi, Wujun; Pei, Cuiying; Wen, Chenhaoping; Gao, Lingling; Zhao, Yi; Yin, Qiangwei; Wu, Yueshen; Li, Gang; Lei, Hechang; Li, Jun; et al.
Abstract: Superconductivity in topological kagome metals has recently received great research interests. Here, charge density wave (CDW) orders and the evolution of superconductivity under various pressures in CsV3 Sb5 single crystal with V kagome lattice are investigated. By using high‐resolution scanning tunneling microscopy/spectroscopy (STM/STS), two CDW orders in CsV3 Sb5 are observed which correspond to 4a × 1a and 2a × 2a superlattices. By applying pressure, the superconducting transition temperature T c is significantly enhanced and reaches a maximum value of 8.2 K at around 1 GPa. Accordingly, CDW state is gradually declined as increasing the pressure, which indicates the competing interplay between CDW and superconducting state in this material. The broad superconducting transitions around 0.4–0.8 GPa can be related to the strong competition relation among two CDW states and superconductivity. These results demonstrate that CsV3 Sb5 is a new platform for exploring the interplay between superconductivity and CDW in topological kagome metals. Abstract : 4a × 1a and 2a × 2a charge density wave (CDW) orders are observed in kagome superconductor CsV3 Sb5 single crystal. A dome‐shaped phase diagram accompanying the suppression of CDW state reveals a complex landscape of electronic states that can co‐exist on a kagome lattice and compete with superconductivity, offering a new platform to investigate the interplay between superconductivity, CDW, and nontrivial topological electronic structure.